2023
DOI: 10.3389/fpsyg.2023.1176970
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and professional identity among male nurses and male nursing students: mediating roles of perceived prejudice and psychological distress

Abstract: IntroductionThere are not enough nurses around the world, and there are even fewer male nurses. It has not been easy for men to become nurses because of stereotypes about the roles of men and women in the workplace, which lead to prejudice and discrimination. This study explored how the self-esteem of male nurses and male nursing students affects their professional identity in an environment where stereotypes and social prejudice exist. This study also examined the differences of relevant variables in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…These findings contrast with research conducted on Egyptian nursing students, which found that both male and female nursing students had moderate levels of self-esteem [ 43 ]. One explanation for that result is the presence of other factors that affect self-esteem, such as perceived prejudice, exposure to professional stress, and professional identity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with research conducted on Egyptian nursing students, which found that both male and female nursing students had moderate levels of self-esteem [ 43 ]. One explanation for that result is the presence of other factors that affect self-esteem, such as perceived prejudice, exposure to professional stress, and professional identity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%